Symptoms of mental illness among university student-athletes during the second wave of the COVID-19 pandemic lockdown in Canada - Boudreault, Véronique; Labossière, Sophie; Gauthier, Véronique; Brassard, Sophie; Couture, Sophie; Dionne, Frédérick; Laurier, Catherine; Durand-Bush, Natalie (Frontiers in Sports and Active Living, 2022)
The COVID-19 pandemic lockdown disrupted the university sports season and had negative consequences on the academic and personal life of university student-athletes, resulting in several psychological challenges. The goal of this study is to document the symptoms of mental illness among university student-athletes during the second wave of the COVID-19 pandemic lockdown in Canada. It aims to a) assess the prevalence of mental illness symptoms (anxiety, depression, disordered eating, and dangerous drinking) among university student-athletes and b) identify which sociodemographic and sports characteristics, pandemic impacts, and levels of perceived stress most influence these symptoms. A total of 424 university student-athletes completed an online survey, which included questions on mental illness and the impact of the pandemic lockdown. The results revealed a notable prevalence of the symptoms of mental illness; depressive symptoms are reported by 37.9% of the participants, anxiety symptoms by 24.9%, dangerous drinking symptoms by 10.1%, and disordered eating by 8.6%. In addition, being female (OR = 0.56, 95% CI [0.33, 0.95]) or a member of a visible minority group (OR = 2.63, 95% CI [1.02, 6.78]) are significantly associated with the presence of depressive symptoms. Low academic motivation has a significant negative influence on the presence of depressive (OR = 3.37, 95% CI [1.82, 6.25]) and anxiety symptoms (OR = 2.75, 95% CI [1.35, 5.62]). However, the presence of perceived stress was strongly associated with depressive (OR = 7.07, 95% CI [3.26, 15.35]), anxiety (OR = 6.51, 95% CI [3.30, 12.84]), and dangerous drinking symptoms (OR = 5.74, 95% CI [2.51, 13.14]). This study advocates for specific mental illness prevention and treatment resources tailored to the unique needs of university student-athletes. Accordingly, partnerships and practical interventions to support university student-athletes’ mental health are presented.